Chiral Calix[3]pyrrole Derivatives: Synthesis, Racemization Kinetics, and Ring Expansion to Calix[9]‐ and Calix[12]pyrrole Analogues. (28th February 2023) - Inaba, Yuya; Yang, Jian; Kakibayashi, Yu; Yoneda, Tomoki; Ide, Yuki; Hijikata, Yuh; Pirillo, Jenny; Saha, Ranajit; Sessler, Jonathan L.; Inokuma, Yasuhide
Abstract: Chiral pyrrolic macrocycles continue to attract interest. However, their molecular design remains challenging. Here, we report a calixpyrrole‐based chiral macrocyclic system, calix[1]furan[1]pyrrole[1]thiophene (1 ), synthesized from an oligoketone. Macrocycle 1 adopts a partial cone conformation in the solid state, and undergoes racemization via ring inversion. Molecular dynamics simulations revealed that inversion of the thiophene is the rate determining step. Pyrrole N ‐methylation suppressed racemization and permitted chiral resolution. Enantioselective N ‐methylation also occurred in the presence of a chiral ammonium salt, although the stereoselectivity is modest. A unique feature of 1 is that it acts as a useful synthetic precursor to yield several calix[ n ]furan[ n ]pyrrole[ n ]thiophene products ( n =2–4), including a calix[12]pyrrole analogue that to our knowledge constitutes the largest calix[ n ]pyrrole‐like species to be structurally characterized. Abstract : An inherently chiral calix[3]pyrrole derivative was synthesized from a polyketone precursor. Although the macrocycle racemizes through ring inversion at room temperature, N ‐methylation effectively suppressed the racemization, allowing chiral resolution of the enantiomers. Ring expansion reaction allowed access to calix[9]‐ and calix[12]pyrrole‐type macrocycles, the largest of which was characterized by an X‐ray diffraction analysis.